Prevalence of psychological factors in chronic dermatoses - Coskun, BK; Atmaca, M; Saral, Y; Coskun, N (Taylor & Francis as, 2005)
Aim: To investigate, retrospectively, psychiatric consultation results of inpatients staying in Firat University Dermatology Clinic. Materials and method: Records of 520 inpatients who were treated in Firat University Dermatology Clinic between May 2000 and May 2003 were examined and their psychiatric consultation reports were retrospectively evaluated. Results: Of the 520 patients who were included in the study, 272 were female and 248 were male. Ninety-two patients were asked to have psychiatric consultation and when consultation results of these patients were examined it was seen that 67 of them (61.7%) were given a psychiatric diagnosis. Of the 67 patients who were given a psychiatric diagnosis, 34 (50.7%) were female and 33 (49.3%) were male. Mean age of the patients was 39.4 ( the youngest being 24 and the oldest 63). It was established that 35.9% of patients ( 24 individuals) were diagnosed as depressive disorder, 29.8% ( 20 individuals) as anxiety disorder, 13.4% ( nine individuals) as mixed depressive anxiety disorder, 13.4% ( nine individuals) as borderline personality disorder and 7.5% ( five individuals) as obsessive - compulsive disorder, and that psychiatric treatment was started in 91% of patients. Dermatological diagnoses of patients who were given psychiatric diagnoses were as follows in order of frequency: psoriasis in 22 patients (32.9%), urticaria in 31 patients (46.2%), prurigo nodularis in five patients (7.4%) and others in nine patients (13.5%), respectively. Conclusions: Dermatological diseases and psychiatric disorders frequently go together. Psychiatric treatment was started in a high number of patients who were given psychiatric diagnoses and had dermatological problems in the present study. Referring patients with chronic dermatological problems to the psychiatry clinic with a view to supporting their dermatological treatments, we believe, will increase the success rate of dermatosis treatment.
Keywords: psychological factors; chronic dermatoses